Herbivory - Barros, Breno; Fernandes, Marcus E. B. (IntechOpen, 2013)
Studies of herbivory provide important insights into fundamental questions in many areas of the biological sciences. The focus on natural systems is more effective for the prediction of potential changes in ecosystems, given that agricultural systems are designed to create an equilibrium that optimizes the productive process. Given the ramifications of the processes related to herbivory, studies based on complementary approaches are necessary for a better understanding of the different aspects of the ecological process. This book attempts to expand on these different aspects of herbivory by presenting a multidisciplinary approach to a number of different themes, focusing on topics that range from basic research in natural habitats to the intrinsic relationships between animals and plants in agricultural systems.